Recognition of child maltreatment as a result of parents presenting to hospital. (4th April 2011) - Hodes, D; Smith, P; Begent, J; Gilbert, R
Abstract : Aims: There is increasing recognition of the safeguarding needs of children whose parents are affected by domestic violence (DV), mental health problems and substance misuse highlighted in Local Safeguarding Board Child Protection Procedures. Acute hospital trusts maybe one of the first points of recognition of the parental problems. However there is little evidence demonstrating awareness among staff of adult presentations might lead to protection of their vulnerable children. Our hospital procedures suggest a child and family referral to social care in these situations. We aimed to measure the pattern of referrals to the hospital child and family social worker when the presenting adult causes concern about their children. Method: All emergency department, paediatric and other departmental staff were trained to consider the implications of adult presentation with DV, alcohol/drug misuse, mental health problems for their children. Data about such referrals is collected monthly. Results: Referrals increased between 2008 and 2009. Of cases reported to named nurse in 2008, 94/320 (30%) were children who were reported through their parents presenting to the hospital. The total numbers referred in 2009 increased to 549 with 164 referred through their parents with the proportion remaining at 30%. The concerns were because of DV/assault, 33 (35%) in 2008 and 56 (34%) in 2009; mental health problems increased from 14 (15%) in 2008 to 43 (26%) in 2009. For substance misuse and overdose the proportion was the approximately the same between the years, average 19% and 8% respectively. There was improved data collection with 23% classified as other in 2008 but 13% in 2009. There was a parallel doubling in the proportion of referrals that came from the hospital to the local Child and Family Social Care; 11% in 2005 versus 22% in 2009. Conclusions: The needs of children whose parents present to hospital are rarely considered. The audit shows that with increased training and hospital guidelines, referrals related to parent presentations increase. Many of these cases required liaison with social care, police, education and primary care.